(3GdUMjaI GdQMeIs - (3eLghds
(3ChdgG (B:s
(3afGOGgG eGdc SQgG hLgQgG s
(3BNQgG (B:s
(3eKd eG Ydjg GdQLd hYHOg hCeG CadGWhf s
(3Vef eLehY , JQJjHgG (B: (3GdUMjaI GdKGfjIs
(3efbhdI ef NW CHj HcQ eMeO Hf GdMSf GdfMhis
(3fSNI KGdKIs
(3fbdJ ef GdjhfGfjI Edi GdYQHjIs
(3JHUQI GdYfhGf (B:s
(3JQLeI(B/(3fbds
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdadSaI hGdefWbs